Auditory resting-state functional connectivity in tinnitus and modulation with transcranial direct current stimulation. (2nd December 2015) - Minami, Shujiro B.; Oishi, Naoki; Watabe, Takahisa; Uno, Kimiichi; Kaga, Kimitaka; Ogawa, Kaoru
Abstract: Conclusions: The functional connectivity (FC) between the right and left auditory cortex is weak in tinnitus patients. Transcranial direct current stimulation (tDCS) over the auditory cortex has potential as a tool to modulate auditory-based FC. Objective: This study investigated the effects of applying tDCS in tinnitus patients, and searched for modulation of brain networks in resting-state functional magnetic resonance imaging (rs-fMRI) through an analysis of FC with the stimulated brain region. Subjects and methods: Nine male patients with chronic tinnitus and 10 male volunteers with normal hearing were enrolled. The subjects were evaluated with rs-fMRI immediately before and after tDCS. The tinnitus patients filled out the self-evaluation questionnaires designed to measure tinnitus conditions before tDCS treatment and 1 week afterwards. Results: The FC between the right and left auditory cortex was significantly weaker in tinnitus patients than in controls. After tDCS treatment, in the tinnitus group, the primary auditory cortex showed a reduction in the amount of statistically significant connectivity with the somatosensory area and motor area, but maintained strong significant connectivity ( p < 0.005) with the auditory area and insular cortex. In contrast, in the control group, there remained strong significant connectivity between the primary auditory cortex and the somatosensory area, motor area, insular cortex, and auditory area.